1995
DOI: 10.1093/clinids/21.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloidiasis in Patients with Hematologic Malignancies

Abstract: We retrospectively studied 343 consecutive patients treated between 1979 and 1992. Ninety patients whose stool was not examined were excluded. Fifty-three patients with strongyloidiasis were compared with 200 controls with regard to outcomes and the following characteristics: age, sex, underlying disease, use of corticosteroids, abdominal pain, diarrhea, fever, pulmonary symptoms, and eosinophilia. Patients with strongyloidiasis more commonly had eosinophilia (P = .01) and fever (P = .03). There was a single b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 8 publications
2
40
0
4
Order By: Relevance
“…The prevalence in the presente series, 8.3% is much lower than 21% found in a retrospective study in a similar population in Rio de Janeiro (RJ) 11 and there was agreement in low incidence of complicated infection: zero and 1.9% in RJ. One important difference between these data is the retrospective design of RJ study and the smaller sample and prospective present study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The prevalence in the presente series, 8.3% is much lower than 21% found in a retrospective study in a similar population in Rio de Janeiro (RJ) 11 and there was agreement in low incidence of complicated infection: zero and 1.9% in RJ. One important difference between these data is the retrospective design of RJ study and the smaller sample and prospective present study.…”
Section: Discussionsupporting
confidence: 64%
“…Samples defined by a disease, like AIDS, may not have an elevated prevalence of strongyloidosis, contrary to what would be expected 2 6 . Even when prevalence is high, hyperinfection and/or disseminated disease is apparently not proportionally more frequent 11 . These data should not shadow the importance of a single episode of hyperinfection and disseminated strongyloidosis, with its severe morbidity and p o t e n t i a l l o w r e s p o n s e t o p r o l o n g e d treatment 12 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are the immunosupressor drugs most specifically associated with the transformation of chronic strongyloidiasis into hyperinfection, 21 doubling or tripling this risk. 22 Hyperinfection is a life-threatening condition with an approximately 50% mortality rate, generally due to Gram-negative septicemia. 23 A TH2-type cellular immune response is normally required to control parasite infections [24][25][26] through the production of cytokines and Immunoglobulin E, which eliminate the organism.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite all these limitations of screening and the high incidence of strongyloidiasis in many parts of the world, disseminated strongyloidiasis and hyperinfection syndrome seem to be unusual, even in endemic areas. 5 None of our patients enrolled in the prospective study, including those who subsequently underwent autologous SCT and the two patients with strongyloidiasis diagnosed during the neutropenic phase of SCT developed a syndrome of hyperinfection or disseminated strongyloidiasis. 3,4 After having completed these studies, we concluded that, given the low incidence of complications and the endemic character of strongyloidiasis in Brazil, no routine screening or prophylaxis would be performed.…”
mentioning
confidence: 99%